2012
DOI: 10.2355/isijinternational.52.1513
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Impurities in Pure Iron Obtained by Hydrogen Reduction

Abstract: Hydrogen itself is not a primary energy and needs an energy for its production, which means that CO2 will be exhausted during the production process, more or less. However, when a Green Hydrogen can be produced, it is a best way to use the hydrogen instead of carbon.In this study, two kinds of iron ore were reduced and melted both under hydrogen and carbon atmosphere. The obtained iron metal under hydrogen atmosphere was quite pure one. The impurities in the metal were chemically and thermodynamically analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…(8) The amount of WGSR occurring with gasification reaction was about 1.5 times larger than that of single WGSR. graphite (mol/s/cm 3 -bed) R W : Rate of water gas reaction I (mol/s/cm 3 -bed) R WC : Rate of water gas reaction I of coke (mol/s/cm 3bed) R WG : Rate of water gas reaction I of graphite (mol/s/ cm 3 -bed) R W2 : Rate of water gas reaction II (mol/s/cm 3 -bed) R W2C : Rate of water gas reaction II of coke (mol/s/cm 3bed) R W2G : Rate of water gas reaction II of graphite (mol/s/ cm 3 -bed) R sh-i : Rate of inverse water gas shift reaction (mol/s/ cm 3…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(8) The amount of WGSR occurring with gasification reaction was about 1.5 times larger than that of single WGSR. graphite (mol/s/cm 3 -bed) R W : Rate of water gas reaction I (mol/s/cm 3 -bed) R WC : Rate of water gas reaction I of coke (mol/s/cm 3bed) R WG : Rate of water gas reaction I of graphite (mol/s/ cm 3 -bed) R W2 : Rate of water gas reaction II (mol/s/cm 3 -bed) R W2C : Rate of water gas reaction II of coke (mol/s/cm 3bed) R W2G : Rate of water gas reaction II of graphite (mol/s/ cm 3 -bed) R sh-i : Rate of inverse water gas shift reaction (mol/s/ cm 3…”
Section: Discussionmentioning
confidence: 99%
“…Kashiwaya 1,3) has shown the benefit of reduction by pure hydrogen, in which the rate of reduction is faster than that of CO reduction and the clean iron can be obtained. Before usage of pure hydrogen, we should understand the reactions in CO-CO 2 -H 2 -H 2 O system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kashiwaya et al reported the behavior of impurities when iron ore was reduced using hydrogen or carbon in the range 1 173-1 373 K as part of direct steelmaking. 9) The iron ore was first reduced below the melting point of iron, and the reduced iron was then melted at 1 873 K in the same crucible without removing the slag. The silicon and manganese contents of the iron reduced using hydrogen were lower than those of the iron reduced using carbon; however, the difference between the phosphorus contents of the iron reduced using hydrogen or carbon was insignificant, indicating that the phosphorus had readily moved to the metal phase during remelting.…”
Section: Introductionmentioning
confidence: 99%